Integrating halal principles to strengthen food safety literacy among vocational pesantren school students in Blitar regency - Nur Aini Mahmudah; Aditya Wirawantoro Putra; David Kurniawan; Nur Agustin Mardiana; Anang Widigdyo; Panji Purnomo (Universitas Muhammadiyah Malang, 2025)
Food safety and halal compliance are critical components of public health, particularly in Indonesia, which has the world’s largest Muslim population. This study aimed to enhance food safety literacy among high school students by integrating halal principles through a community service-based educational intervention at a vocational pesantren school - SMKI Anharul Ulum Blitar. A total of 29 students and 3 teachers participated in seminars, practice sessions, and discussions covering food safety fundamentals, halal principles, product identification, and practical hygiene applications. Pre- and post-intervention assessments measured knowledge, integrative reasoning, product identification skills, and practical application. Results indicated substantial improvements in basic knowledge, with average scores increasing from 71.6 to 94.8 for food safety (32.5% increase) and from 57.5 to 95.4 for halal principles (66% increase). Integration of food safety and halal knowledge showed a modest gain (14.3%), suggesting that participants still viewed these domains separately. Skills in identifying halal products improved moderately (11.5%), while practical application of food safety and halal principles increased by 36.4%. The findings highlight that while knowledge acquisition is achievable through short-term interventions, translating this knowledge into confident, practical behavior requires hands-on learning, repeated practice, and reinforcement. Incorporating activities such as label-reading exercises, product case studies, and supervised demonstrations can enhance participants’ competence and confidence. This study demonstrates the effectiveness of integrating halal principles into food safety education, emphasizing the importance of experiential learning and structured guidance to foster sustainable behavioral change. The results provide a model for school-based programs aiming to improve food safety literacy and halal awareness among the younger generation in Indonesia.